Positive electrode active material, preparation method thereof, positive electrode sheet, battery, and electric device
Patent Information
- Application Number
- CN202410281506.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-11
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2044-03-11
AI Technical Summary
然而,钠电池的电化学性能不佳,导致其在实际应用中受到限制
Smart Images

Figure CN120657067B_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of battery technology, specifically relating to positive electrode active materials and preparation methods, positive electrode sheets, batteries, and electrical devices. Background Technology
[0002] Sodium-ion batteries, as a representative of rechargeable batteries, have been applied in various fields such as energy storage power systems (e.g., hydropower, thermal power, wind power, and solar power plants), electric vehicles, and aerospace. Compared to lithium-ion batteries, sodium-ion batteries have a cost advantage in raw materials, especially since sodium salts, the main component of the positive electrode active material, are more abundant and their price is much lower than that of lithium salts used in the positive electrode active material of lithium-ion batteries. This makes the cost of sodium-ion battery positive electrode active materials lower than that of lithium-ion batteries. However, the poor electrochemical performance of sodium-ion batteries limits their practical applications. Summary of the Invention
[0003] The purpose of this application is to provide a positive electrode active material and its preparation method, a positive electrode sheet, a battery, and an electrical device. The positive electrode active material has excellent air stability, which can improve the cycle stability of the battery.
[0004] A first aspect of this application provides a positive electrode active material, the positive electrode active material comprising a bulk phase and a coating phase located on at least a portion of its surface, wherein the bulk phase comprises Na. x1 Mn y1 X z O 2+δ1 , the Na x1 Mn y1 X z O 2+δ1 The coating phase includes the O'3 phase, with a 0.8 ≤ x1 ≤ 1, 0.8 ≤ y1 ≤ 1, 0 ≤ z ≤ 0.2, and -0.1 ≤ δ1 ≤ 1. X includes one or more of Ti, Zr, Ge, and Sn. The coating phase includes Na. x2 Mn y2 X z O 2+δ2 , the Na x2 Mn y2 X z O 2+δ2 This includes the P2 phase, with a range of 0.4 ≤ x² ≤ 0.7, 0.85 ≤ y² ≤ 1, and -0.1 ≤ δ² ≤ 1. Therefore, by forming a coating phase on at least a portion of the surface of the positive electrode active material, the coating phase reduces the probability of sodium in the bulk phase reacting with air. Furthermore, the coating phase itself is sodium-deficient, resulting in a lower probability of reaction with air, thereby improving the air stability of the positive electrode active material and enhancing the cycle stability of the battery.
[0005] According to some embodiments of this application, the volume average particle size D of the positive electrode active material V The thickness of 50 is 0.2μm-3μm. As a result, the sodium ion conduction distance within the positive electrode active material is short and there are fewer surface side reactions, which promotes the specific capacity of the positive electrode active material and improves the capacity retention rate of batteries containing it.
[0006] According to some embodiments of this application, the space groups of the O'3 phase and the P2 phase are C2 / m and P63 / mmc, respectively. Thus, the O'3 phase has a high sodium content, which can improve the battery capacity; the P2 phase has a large interlayer spacing, which can improve the battery's rate performance and cycle performance.
[0007] According to some embodiments of this application, the peak intensity of 001 in the X-ray diffraction pattern of the O'3 phase is S1, and the peak intensity of 002 in the X-ray diffraction pattern of the P2 phase is S2, where S1 and S2 satisfy 2 ≤ S1 / S2 ≤ 6; the 2θ value corresponding to the 001 peak in the X-ray diffraction pattern is 15.8°-16.8°, and the 2θ value corresponding to the 002 peak is 15.3°-16.3°. This improves the specific capacity of the positive electrode active material, increases the thickness and uniformity of the coating phase, and enhances the air stability of the positive electrode active material.
[0008] According to some embodiments of this application, the peak intensity of 001 in the X-ray diffraction pattern of the O'3 phase is S1, and the peak intensity of 002 in the X-ray diffraction pattern of the P2 phase is S2, where S1 and S2 satisfy 3 ≤ S1 / S2 ≤ 4.5; the 2θ value corresponding to the 001 peak in the X-ray diffraction pattern is 15.8°-16.8°, and the 2θ value corresponding to the 002 peak is 15.3°-16.3°. This improves the specific capacity of the positive electrode active material, increases the thickness and uniformity of the coating phase, and enhances the air stability of the positive electrode active material.
[0009] A second aspect of this application provides a method for preparing a positive electrode active material, comprising: mixing a sodium source and a manganese source, performing a first sintering in an inert atmosphere to form a bulk phase; and performing a second sintering of the bulk phase in an oxygen-containing atmosphere to form a coating phase on at least a portion of the surface of the bulk phase; wherein the bulk phase comprises Na x1 Mn y1 O 2+δ1 , the Na x1 Mn y1 O 2+δ1 It includes the O'3 phase, 0.8≤x1≤1, 0.8≤y1≤1, -0.1≤δ1≤1; the coating phase includes Na. x2 Mn y2 O 2+δ2 , the Na x2 Mn y2 O 2+δ2The mixture includes a P2 phase, with a molecular weight distribution of 0.4 ≤ x² ≤ 0.7, 0.85 ≤ y² ≤ 1, and -0.1 ≤ δ² ≤ 1; or, a sodium source, a manganese source, and an X source are mixed and sintered for the first time in an inert atmosphere to form a bulk phase; the bulk phase is then sintered for the second time in an oxygen-containing atmosphere to form a coating phase on at least a portion of the surface of the bulk phase; wherein the bulk phase includes Na. x1 Mn y1 X z O 2+δ1 , the Na x1 Mn y1 X z O 2+δ1 The coating phase includes the O'3 phase, with 0.8 ≤ x1 ≤ 1, 0.8 ≤ y1 ≤ 1, 0 < z ≤ 0.2, -0.1 ≤ δ1 ≤ 1, and X includes one or more of Ti, Zr, Ge, and Sn; the coating phase includes Na. x2 Mn y2 X z O 2+δ2 , the Na x2 Mn y2 X z O 2+δ2 This includes the P2 phase, with a content of 0.4 ≤ x² ≤ 0.7, 0.85 ≤ y² ≤ 1, and -0.1 ≤ δ² ≤ 1. Thus, by secondary sintering, a coating phase is formed on at least a portion of the surface of the bulk phase. On the one hand, the coating phase reduces the probability of sodium in the bulk phase reacting with air through "coating." On the other hand, the coating phase itself has a low sodium content, further reducing the probability of reaction with air. This improves the air stability of the positive electrode active material and enhances the cycle stability of the battery.
[0010] According to some embodiments of this application, the conditions for the first sintering include: a temperature of 800℃-1000℃ and a time of 12h-18h. This results in the formation of a sufficient O'3 phase, improving the specific capacity of the positive electrode active material.
[0011] According to some embodiments of this application, the conditions for the first sintering include: a temperature of 850℃-950℃ and a time of 13h-17h. This results in the formation of a sufficient O'3 phase, improving the specific capacity of the positive electrode active material.
[0012] According to some embodiments of this application, the oxygen-containing atmosphere includes oxygen or air. Thus, the surface Mn 3+ Oxidized by oxygen to Mn 4+ Meanwhile, surface Na + The sodium-containing P2 phase (Na) with a lower sodium content is formed in situ on the surface of the bulk phase after the phase is released. x The MnO2 structure improves the air stability of the positive electrode active material.
[0013] According to some embodiments of this application, the conditions for the second sintering include: a temperature of 900℃-1000℃ and a time of 8h-15h. Therefore, by keeping the temperature and time of the second sintering within the above range, a uniform coating phase can be formed on the surface of the bulk phase of the positive electrode active material, thereby improving the air stability of the positive electrode active material.
[0014] According to some embodiments of this application, the conditions for the second sintering include: a temperature of 900℃-950℃ and a time of 9h-12h. Therefore, by keeping the temperature and time of the second sintering within the above range, a uniform coating phase can be formed on the surface of the bulk phase of the positive electrode active material, thereby improving the air stability of the positive electrode active material.
[0015] According to some embodiments of this application, the method satisfies one or more of the following conditions: the sodium source includes one or more of Na2CO3, NaHCO3, NaOH, and Na2O2; the manganese source includes one or more of Mn2O3, Mn3O4, MnO, and MnO2. This improves the specific capacity of the positive electrode active material.
[0016] According to some embodiments of this application, the amounts of the sodium source and the manganese source are such that the atomic molar ratio of Na to Mn is 1:0.8-1.2.
[0017] A third aspect of this application provides a positive electrode sheet, comprising the positive electrode active material provided in the first aspect of this application or the positive electrode active material prepared by the method provided in the second aspect of this application. Therefore, the positive electrode active material exhibits excellent air stability, which can improve the structural stability of the positive electrode sheet and reduce the impact of the reaction between the positive electrode active material and air on the positive electrode sheet.
[0018] A fourth aspect of this application provides a battery including the positive electrode provided in the third aspect of this application. Therefore, the battery exhibits excellent cycle stability.
[0019] The fifth aspect of this application provides an electrical device, including the battery provided in the fourth aspect of this application.
[0020] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of this application. Attached Figure Description
[0021] The above and / or additional aspects and advantages of this application will become apparent and readily understood from the description of the embodiments in conjunction with the following drawings. The drawings are for illustrative purposes only and are not intended to limit the scope of this application.
[0022] Figure 1 This is a schematic diagram of the structure of the positive electrode active material according to one embodiment of this application.
[0023] Figure 2 This is a schematic diagram of the process for preparing a positive electrode active material according to one embodiment of this application.
[0024] Figure 3 This is a schematic diagram of a battery according to one embodiment of this application.
[0025] Figure 4 yes Figure 3 An exploded view of a battery according to one embodiment of this application is shown.
[0026] Figure 5 This is a schematic diagram of a battery module according to one embodiment of this application.
[0027] Figure 6 This is a schematic diagram of a battery pack according to one embodiment of this application.
[0028] Figure 7 yes Figure 6 An exploded view of a battery pack according to one embodiment of this application is shown.
[0029] Figure 8 This is a schematic diagram of an electrical device in which a battery is used as a power source according to one embodiment of this application.
[0030] Figure 9 This is the XRD pattern of the positive electrode active material in Example 1.
[0031] Figure 10 This is the XRD pattern of the positive electrode active material in Comparative Example 1.
[0032] Figure 11 This is a comparison chart of the XRD test results of the positive electrode active materials in Examples 1 and Comparative Example 1.
[0033] Figure 12 This is a SEM image of the positive electrode active material in Example 1 after being placed at room temperature for 10 days.
[0034] Figure 13 This is a SEM image of the positive electrode active material in Comparative Example 1 after being placed at room temperature for 10 days.
[0035] Explanation of reference numerals in the attached figures:
[0036] 1: Battery; 2: Battery module; 3: Battery pack; 4: Upper casing; 5: Lower casing; 51: Housing; 52: Electrode assembly; 53: Cover plate; 11: Positive electrode active material; 111: Bulk phase; 112: Coated phase. Detailed Implementation
[0037] The present application will be further described below with reference to specific embodiments. It should be understood that these specific embodiments are for illustrative purposes only and are not intended to limit the scope of the present application.
[0038] In this application, the reference to "embodiment" means that a specific feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a mutually exclusive, independent, or alternative embodiment. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described in this application can be combined with other embodiments.
[0039] The "range" disclosed in this application is defined in the form of a lower limit and / or an upper limit. A given range is defined by selecting a lower limit and / or an upper limit, which defines the boundary of the particular range. Ranges defined in this way may or may not include endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form an undefined range, and any lower limit can be combined with other lower limits to form an undefined range. Similarly, any upper limit can be combined with any other upper limit to form an undefined range. Furthermore, each individually disclosed point or single value can itself serve as a lower limit or upper limit, combined with any other point or single value, or combined with other lower limits or upper limits to form an undefined range.
[0040] Unless otherwise specified, all embodiments and optional embodiments of this application may be combined with each other to form new technical solutions, and such technical solutions should be considered to be included in the disclosure of this application.
[0041] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions, and such technical solutions shall be deemed to be included in the disclosure of this application.
[0042] Unless otherwise specified, in this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. Additionally, the character " / " in this document generally indicates that the preceding and following related objects have an "or" relationship.
[0043] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used in this application is for the purpose of describing particular embodiments only and is not intended to limit this application; the terms "comprising" and "having," and any variations thereof, in the specification and claims of this application are intended to cover non-exclusive inclusion. Unless otherwise stated, the terms used in this application have their commonly understood meanings as understood by one of ordinary skill in the art. Unless otherwise stated, the numerical values of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (e.g., they can be tested according to the methods given in the embodiments of this application).
[0044] Currently, judging from market trends, battery applications are becoming increasingly widespread. Batteries are not only used in energy storage systems such as hydropower, thermal power, wind power, and solar power plants, but also extensively in electric vehicles such as electric bicycles, electric motorcycles, and electric cars, as well as in military equipment and aerospace. With the continuous expansion of battery applications, market demand is also constantly increasing.
[0045] Sodium is an abundant and widely distributed element, and its lower cost, coupled with the similarity in working principle between sodium-ion batteries and lithium-ion batteries, has led to its increasing attention and research. Among the positive electrode active materials for sodium-ion batteries, manganese-based layered oxides, particularly the O'3 phase, offer advantages in terms of high specific capacity and low cost. However, due to the high sodium content in the O'3 phase, sodium tends to accumulate on the surface of the positive electrode active material during preparation. When exposed to air, sodium readily precipitates and reacts with carbon dioxide and water, forming sodium carbonate and sodium hydroxide on the surface. This results in a high residual alkali content in the positive electrode active material, which further reacts with carbon dioxide and water, leading to poor air stability.
[0046] This application proposes a positive electrode active material, the bulk phase of which includes an O'3 phase with a high sodium content, and at least a portion of the surface of the bulk phase has a coating phase, which is a sodium-deficient P2 phase. On the one hand, the coating phase can reduce the probability of sodium in the bulk phase reacting with air by "coating". On the other hand, the coating phase itself is sodium-deficient, which can reduce the probability of sodium reacting with air, reduce the content of residual alkali generated on the surface of the positive electrode active material due to the reaction of sodium with carbon dioxide and water in the air, thereby reducing the risk of residual alkali reacting further with air, improving the air stability of the positive electrode active material, and thus improving the cycle stability of the battery.
[0047] The positive electrode active material proposed in this application can be used in batteries, which can be used in electrical devices that use batteries as a power source or in various energy storage systems that use batteries as energy storage elements. Electrical devices can include, but are not limited to, mobile phones, tablets, laptops, electric toys, power tools, electric vehicles, electric cars, ships, spacecraft, etc. Electric toys can include stationary or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys, etc. Spacecraft can include airplanes, rockets, space shuttles, and spacecraft, etc.
[0048] The first aspect of this application discloses a positive electrode active material, referring to... Figure 1 The positive electrode active material 11 includes a bulk phase 111 and a coating phase 112 located on at least a portion of its surface, wherein the bulk phase includes Na. x1 Mn y1 X z O 2+δ1 , the Na x1 Mn y1 X z O 2+δ1 The coating phase includes the O'3 phase, with a 0.8 ≤ x1 ≤ 1, 0.8 ≤ y1 ≤ 1, 0 ≤ z ≤ 0.2, and -0.1 ≤ δ1 ≤ 1. X includes one or more of Ti, Zr, Ge, and Sn. The coating phase includes Na. x2 Mn y2 X z O 2+δ2 , the Na x2 Mn y2 X z O 2+δ2 Including phase P2, 0.4≤x2≤0.7, 0.85≤y2≤1, -0.1≤δ2≤1.
[0049] The positive electrode active material proposed in this application has a sodium-deficient coating phase on at least a portion of its bulk surface. On one hand, the coating phase reduces the probability of sodium in the bulk reacting with carbon dioxide and water in the air. On the other hand, the P2 phase has a lower sodium content, and compared to the O'3 phase, the surface of the positive electrode active material is sodium-deficient. This reduction in sodium content decreases the probability of sodium reacting with carbon dioxide and water, thereby improving the air stability of the positive electrode active material and the cycle stability of the battery. The larger interlayer spacing of the P2 phase increases the diffusion rate of sodium ions, further improving the rate performance of the battery.
[0050] The phase testing method in this application is as follows: The sample to be tested is ground finely in an agate mortar and passed through a 350-mesh sieve in a drying room or glove box. An appropriate amount of the sieved sample is placed in the center of the sample holder groove, ensuring the loose sample powder is slightly higher than the sample holder plane. A glass slide is then gently pressed against the sample surface to level it with the frame plane, and excess powder is scraped off. After sample preparation, a Brucker D8A_A25 X-ray powder diffractometer from Brucker AxS (Germany) is used with CuK... α X-rays are the radiation source, and the wavelength of the X-rays is... The XRD pattern was tested with a scanning angle of 5°-60° and a scanning rate of 4° / min. The phase state of the positive electrode active material was determined based on the position of the characteristic peaks in the XRD pattern. The characteristic peaks in the range of 42° to 43° indicate that the positive electrode active material is the O'3 phase, and the characteristic peaks in the range of 48° to 50° indicate that the positive electrode active material is the P2 phase.
[0051] In this application, the O'3 phase positive electrode active material refers to a TMO6 octahedral layer with sodium ions octahedral coordination and oxygen ions stacked, with a minimum repeating layer number of 3, ABCABC, belonging to the C2 / m space group; the P2 phase positive electrode active material refers to a TMO6 octahedral layer with sodium ions triangular prism coordination and oxygen ions stacked, with a minimum repeating layer number of 2, ABAB, belonging to the P63 / mmc space group.
[0052] According to some embodiments of this application, 0.8 ≤ x1 ≤ 1, for example, it can be 0.8, 0.82, 0.84, 0.86, 0.88, 0.9, 0.92, 0.94, 0.96, 0.98 or 1, or it can be a range of any of the above values. This increases the battery capacity.
[0053] According to some embodiments of this application, 0.8 ≤ y1 ≤ 1, for example, it can be 0.8, 0.82, 0.84, 0.86, 0.88, 0.9, 0.92, 0.94, 0.96, 0.98, or 1, or it can be a range of any of the above values. Therefore, by keeping the manganese content within the above range, the structural stability of the O'3 phase layered material can be improved, the risk of active metal ion leakage from the positive electrode active material can be reduced, and the cycle stability of the positive electrode active material can be improved.
[0054] According to some embodiments of this application, 0 ≤ z ≤ 0.2, for example, it can be 0, 0.04, 0.08, 0.12, 0.16, or 0.2, or it can be any range of the above values. Therefore, by doping the bulk phase with different amounts of X element, a bulk phase with an O'3 phase can be formed, thereby improving the specific capacity of the positive electrode active material.
[0055] According to some embodiments of this application, -0.1≤δ1≤1, for example, can be -0.1, -0.05, 0, 0.1, 0.3, 0.5, 0.7, 0.9 or 1, or can be a range of any of the above values.
[0056] It should be noted that due to the loss of oxygen in the bulk phase during battery cycling and other processes, the measured oxygen content 2+δ1 in the bulk phase may be less than 2.
[0057] According to some embodiments of this application, 0.4 ≤ x2 ≤ 0.7, for example, it can be 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, or 0.7, or any range of the above values. Therefore, by keeping the sodium content in the P2 phase within the above range, the probability of sodium reacting with carbon dioxide and water in the air is reduced, the air stability of the positive electrode active material is improved, and the battery capacity is increased.
[0058] According to some embodiments of this application, 0.85 ≤ y2 ≤ 1. For example, y2 can be 0.85, 0.87, 0.89, 0.91, 0.93, 0.95, 0.97, 0.99, or 1, or a range of any of the above values. Therefore, by keeping the manganese content within the above range, the structural stability of the P2 phase layered material can be improved, the risk of active metal ion leakage from the positive electrode active material can be reduced, and the cycle stability of the positive electrode active material can be improved.
[0059] According to some embodiments of this application, -0.1≤δ2≤1, for example, can be -0.1, -0.05, 0, 0.1, 0.3, 0.5, 0.7, 0.9 or 1, or can be a range of any of the above values.
[0060] It should be noted that due to the loss of oxygen in the coating phase during battery cycling and other processes, the measured oxygen content 2+δ2 in the P2 phase may be less than 2.
[0061] According to some embodiments of this application, the volume average particle size D of the positive electrode active material V The value 50 can range from 0.2μm to 3μm. For example, it can be 0.2μm, 0.5μm, 1μm, 1.5μm, 2μm, 2.5μm, or 3μm, or any range of the above values. Therefore, the sodium ion conduction distance within the positive electrode active material is short, and there are fewer surface side reactions, which promotes the specific capacity of the positive electrode active material and improves the capacity retention rate of batteries containing it.
[0062] In this application, D v50 refers to the particle size corresponding to a cumulative volume distribution percentage of 50%. For example, according to standard GB / T 19077-2016 / ISO 13320:2009, the particle size is determined using a laser particle size analyzer (Malvern Master Size 2000). The specific testing procedure is as follows: Take an appropriate amount of the sample to be tested (the sample concentration should be 8%-12% with sufficient light-blocking properties), add 20 ml of deionized water, and simultaneously sonicate for 5 minutes (53 kHz / 120 W) to ensure complete dispersion of the sample. Then, measure the sample according to the standard GB / T19077-2016 / ISO 13320:2009.
[0063] According to some embodiments of this application, the space groups of the O'3 phase and the P2 phase are C2 / m and P63 / mmc, respectively. Thus, the O'3 phase has a high sodium content, which can improve the battery capacity; the P2 phase has a large interlayer spacing, which can improve the diffusion rate of sodium ions, thereby improving the rate performance of the battery.
[0064] According to some embodiments of this application, the peak intensity of 001 in the X-ray diffraction pattern of the O'3 phase is S1, and the peak intensity of 002 in the X-ray diffraction pattern of the P2 phase is S2, where S1 and S2 satisfy 2 ≤ S1 / S2 ≤ 6; the 2θ value corresponding to the 001 peak in the X-ray diffraction pattern is 15.8°-16.8°, and the 2θ value corresponding to the 002 peak is 15.3°-16.3°. For example, S1 / S2 can be 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, or 6, or a range of any of the above values. Thus, on the one hand, the content of the bulk phase in the positive electrode active material is increased, thereby increasing the specific capacity of the material; on the other hand, the content of the P2 phase in the positive electrode active material is increased, forming a uniform P2 phase on the surface of the bulk phase, improving the coating effect of the P2 phase, and improving the air stability of the positive electrode active material. According to some specific embodiments of this application, 3 ≤ S1 / S2 ≤ 4.5.
[0065] The second aspect of this application provides a method for preparing the positive electrode active material provided in the first aspect of this application, comprising mixing a sodium source and a manganese source, performing a first sintering in an inert atmosphere to form a bulk phase; and performing a second sintering of the bulk phase in an oxygen-containing atmosphere to form a coating phase on at least a portion of the surface of the bulk phase; wherein the bulk phase includes Na x1 Mn y1 O 2+δ1 , the Na x1 Mn y1 O 2+δ1 It includes the O'3 phase, 0.8≤x1≤1, 0.8≤y1≤1, -0.1≤δ1≤1; the coating phase includes Na. x2 Mn y2 O 2+δ2, the Na x2 Mn y2 O 2+δ2 The mixture includes a P2 phase, with a molecular weight distribution of 0.4 ≤ x² ≤ 0.7, 0.85 ≤ y² ≤ 1, and -0.1 ≤ δ² ≤ 1; or, a sodium source, a manganese source, and an X source are mixed and sintered for the first time in an inert atmosphere to form a bulk phase; the bulk phase is then sintered for the second time in an oxygen-containing atmosphere to form a coating phase on at least a portion of the surface of the bulk phase; wherein the bulk phase includes Na. x1 Mn y1 X z O 2+δ1 , the Na x1 Mn y1 X z O 2+δ1 The coating phase includes the O'3 phase, with 0.8 ≤ x1 ≤ 1, 0.8 ≤ y1 ≤ 1, 0 < z ≤ 0.2, -0.1 ≤ δ1 ≤ 1, and X includes one or more of Ti, Zr, Ge, and Sn; the coating phase includes Na. x2 Mn y2 X z O 2+δ2 , the Na x2 Mn y2 X z O 2+δ2 This includes the P2 phase, with a content of 0.4 ≤ x² ≤ 0.7, 0.85 ≤ y² ≤ 1, and -0.1 ≤ δ² ≤ 1. Thus, by secondary sintering, a coating phase is formed on at least a portion of the surface of the bulk phase. On the one hand, the coating phase reduces the probability of sodium in the bulk phase reacting with air through "coating." On the other hand, the coating phase itself has a low sodium content, further reducing the probability of reaction with air. This improves the air stability of the positive electrode active material and enhances the cycle stability of the battery.
[0066] refer to Figure 2 The following is a detailed description of each step in this application:
[0067] S100: Sodium and manganese sources are mixed and sintered for the first time to prepare bulk phase.
[0068] According to some embodiments of this application, in this step, sodium and manganese sources are mixed and subjected to a first sintering in an inert atmosphere to form a bulk phase, wherein the bulk phase includes Na. x1 Mn y1 O 2+δ1 , the Na x1 Mn y1 O 2+δ1 Including phase O'3, 0.8≤x1≤1, 0.8≤y1≤1, -0.1≤δ1≤1.
[0069] According to some embodiments of this application, sodium source, manganese source, and X source are mixed and subjected to a first sintering in an inert atmosphere to form a bulk phase, wherein the bulk phase includes Na. x1 Mn y1 X z O 2+δ1 , the Na x1 Mn y1 X z O 2+δ1 It includes the O'3 phase, 0.8≤x1≤1, 0.8≤y1≤1, 0<z≤0.2, -0.1≤δ1≤1, and X includes one or more of Ti, Zr, Ge, and Sn.
[0070] According to some embodiments of this application, the conditions for the first sintering include: a temperature of 800℃-1000℃ and a time of 12h-18h.
[0071] As an example, the temperature for the first sintering can be 800℃, 850℃, 900℃, 950℃, or 1000℃, or any range of the above values. According to some specific embodiments of this application, the temperature for the first sintering can be 850℃-950℃.
[0072] As an example, the first sintering time can be 12h, 13h, 14h, 15h, 16h, 17h, or 18h, or can be any range of the above values. According to some specific embodiments of this application, the first sintering time can be 13h-17h.
[0073] Therefore, by keeping the temperature and time of the first sintering within the above range, the content of the O'3 phase in the positive electrode active material can be increased, thereby increasing the specific capacity of the positive electrode active material.
[0074] According to some embodiments of this application, the inert atmosphere may include an inert gas or nitrogen.
[0075] According to some embodiments of this application, the sodium source includes one or more of Na2CO3, NaHCO3, NaOH, and Na2O2.
[0076] According to some embodiments of this application, the manganese source includes one or more of Mn2O3, Mn3O4, MnO, and MnO2.
[0077] According to some embodiments of this application, the amounts of the sodium source and the manganese source are such that the atomic molar ratio of Na to Mn is 1:0.8-1.2. For example, it can be 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, etc., or any range of the above values. This reduces the volatilization of the sodium source during high-temperature sintering and simultaneously lowers the residual alkali content on the surface of the positive electrode active material.
[0078] S200: Perform a second sintering on the bulk phase to prepare the coated phase.
[0079] According to some embodiments of this application, the bulk phase prepared in S100 is subjected to a second sintering in an oxygen-containing atmosphere to form a coating phase on at least a portion of the surface of the bulk phase, the coating phase comprising Na. x2 Mn y2 X z O 2+δ2 , the Na x2 Mn y2 X z O 2+δ2 The coating includes a P2 phase, with a composition of 0.4 ≤ x² ≤ 0.7, 0.85 ≤ y² ≤ 1, 0 ≤ z ≤ 0.2, and -0.1 ≤ δ² ≤ 1. X includes one or more of Ti, Zr, Ge, and Sn. Therefore, on the one hand, the "coating" of the coating phase reduces the probability of sodium in the bulk phase reacting with air; on the other hand, the coating phase itself is sodium-deficient, resulting in a lower probability of reaction with air. This improves the air stability of the positive electrode active material and enhances the cycle stability of the battery.
[0080] According to some embodiments of this application, the conditions for the second sintering include: a temperature of 900℃-1000℃ and a time of 8h-15h.
[0081] As an example, the temperature of the second sintering can be 900℃, 920℃, 940℃, 960℃, 980℃, or 1000℃, or a range of any of the above values. According to some specific embodiments of this application, the temperature of the second sintering can be 900℃-950℃.
[0082] As an example, the second sintering time can be 8h, 9h, 10h, 11h, 12h, 13h, 14h, or 15h, or a range of any of the above values. According to some specific embodiments of this application, the second sintering time can be 9h-12h.
[0083] Therefore, by keeping the temperature and time of the second sintering within the above range, a uniformly coated phase is formed on the surface of the bulk phase, thereby improving the air isolation effect of the coated phase and enhancing the air stability of the positive electrode active material.
[0084] According to some embodiments of this application, the oxygen-containing atmosphere includes oxygen or air.
[0085] A third aspect of this application provides a positive electrode sheet, comprising the positive electrode active material provided in the first aspect of this application or the positive electrode active material prepared by the method provided in the second aspect of this application. Therefore, the positive electrode active material exhibits excellent air stability, which can improve the structural stability of the positive electrode sheet and reduce the impact of the reaction between the positive electrode active material and air on the positive electrode sheet.
[0086] In some embodiments, the positive electrode includes a positive current collector and a positive electrode film layer disposed on at least one side of the positive current collector, the positive electrode film layer containing the positive electrode active material.
[0087] In this application, the positive current collector can be, for example, a metal foil or a composite current collector. The metal foil can be, for example, aluminum foil. The composite current collector can include a polymer base layer and a metal layer formed on at least one side of the polymer base layer. The material of the metal layer includes, but is not limited to, aluminum, aluminum alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys. The polymer material of the polymer base layer can be, for example, polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.
[0088] In some embodiments, the positive electrode active material is the positive electrode active substance in the positive electrode film layer. In addition to this positive electrode active material, the positive electrode film layer may optionally include a conductive agent and / or a binder. As examples, the conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers; the binder may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resins.
[0089] This application does not specifically limit the preparation method of the positive electrode sheet, and it can be prepared by referring to existing methods. For example, the positive electrode slurry is coated on the positive electrode current collector, and then dried and cold-pressed to form the positive electrode sheet. The positive electrode slurry can be formed by dispersing the positive electrode active material, optional conductive agent, optional binder and other components in a solvent (e.g., N-methylpyrrolidone) and stirring evenly.
[0090] Furthermore, the positive electrode sheet of this application does not exclude other additional functional layers besides the positive electrode film layer. For example, the positive electrode sheet may also include a conductive undercoat layer (e.g., composed of a conductive agent and a binder) disposed between the positive current collector and the positive electrode film layer. As another example, the positive electrode sheet may also include a protective layer covering the surface of the positive electrode film layer.
[0091] A fourth aspect of this application provides a battery comprising the positive electrode sheet described in the third aspect of this application.
[0092] In some embodiments, the battery further includes a negative electrode, a separator, and an electrolyte. During charging and discharging, active ions move back and forth between the positive and negative electrodes, inserting and extracting. The electrolyte acts as a conductor of ions between the positive and negative electrodes. The separator, positioned between the positive and negative electrodes, prevents short circuits while allowing ions to pass through.
[0093] [Negative electrode plate]
[0094] In some embodiments, the negative electrode sheet may include a negative current collector and a negative electrode film layer disposed on at least one side of the negative current collector, the negative electrode film layer comprising a negative electrode material.
[0095] In some embodiments, the negative electrode current collector may include a metal foil or a composite current collector. The metal foil may be, for example, copper foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one side of the polymer substrate. The materials of the metal layer include, but are not limited to, copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys. The polymer materials of the polymer substrate include, but are not limited to, polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).
[0096] In this application, the negative electrode material may include negative electrode active materials well known in the art for use in secondary batteries. For example, the negative electrode active material includes one or more of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate, etc. The silicon-based material may include one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may include one or more of elemental tin, tin oxide compounds, and tin alloys.
[0097] In some embodiments, the negative electrode film layer may optionally include a binder. The binder may include, for example, one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0098] In some embodiments, the negative electrode film may optionally include a conductive agent. As an example, the conductive agent may include one or more of superconducting carbon, acetylene black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0099] In some embodiments, the negative electrode film layer may optionally contain other additives, such as thickeners. Specific examples of thickeners include, but are not limited to, sodium carboxymethyl cellulose (CMC-Na).
[0100] This application does not specifically limit the preparation method of the negative electrode sheet, and it can be prepared by referring to existing methods. For example, the negative electrode material, conductive agent, binder and other negative electrode components are dispersed in a solvent (e.g., deionized water) to form a negative electrode slurry; then the negative electrode slurry is coated on a negative electrode current collector, and after drying, cold pressing, etc., a negative electrode sheet is obtained.
[0101] Electrolyte
[0102] In this application, the electrolyte can be selected from existing secondary batteries. In some embodiments, the electrolyte comprises an organic solvent, a sodium salt, and optional additives. The sodium salt includes, but is not limited to, one or more of NaPF6, NaClO4, NaBCl4, NaSO3CF3, and Na(CH3)C6H4SO3. The organic solvents include, but are not limited to, one or more of the following: ethylene carbonate (EC), propylene carbonate (PC), methyl ethyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butyl carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), and diethyl sulfone (ESE).
[0103] In some embodiments, the additives in the electrolyte may include negative electrode film-forming additives and positive electrode film-forming additives; they may also include additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature or low-temperature performance, etc. As an example, the additive may include one or more of the following: vinylene carbonate (VC), vinyl ethylene carbonate (VEC), vinyl sulfate (DTD), propylene sulfate, vinyl sulfite (ES), 1,3-propanesulfonate lactone (PS), 1,3-propenesulfonate lactone (PST), sulfonate cyclic quaternary ammonium salts, succinic anhydride, succinic anhydride (SN), adiponitrile (AND), tris(trimethylsilane) phosphate (TMSP), and tris(trimethylsilane) borate (TMSB).
[0104] [Isolation membrane]
[0105] In this application, the separator is disposed between the positive and negative electrode plates, primarily serving to prevent short circuits between the positive and negative electrodes while allowing active ions to pass through. This application does not impose any particular limitation on the type of separator; various porous separators well-known in the art can be selected. In some embodiments, the separator material may include one or more of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. Furthermore, the separator can be a single-layer film or a multi-layer composite film. When the separator is a multi-layer composite film, the materials of each layer may be the same or different.
[0106] In some embodiments, a ceramic coating and / or a metal oxide coating are also provided on the separator.
[0107] In some implementations, the positive electrode, negative electrode, and separator can be fabricated into an electrode assembly using a winding or stacking process.
[0108] In some implementations, the positive electrode, negative electrode, and separator can be fabricated into an electrode assembly using a winding or stacking process.
[0109] In some embodiments, the battery may include an outer packaging. This outer packaging may be used to encapsulate the electrode assembly and electrolyte described above.
[0110] In some implementations, the battery's outer packaging can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. The battery's outer packaging can also be a soft pack, such as a pouch. The soft pack can be made of plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0111] This application does not impose any particular limitation on the shape of the battery; it can be cylindrical, square, or any other arbitrary shape. For example, Figure 3 The battery 5 is a square structure, which serves as an example.
[0112] In some implementations, refer to Figure 4 The outer packaging may include a housing 51 and a cover plate 53. The housing 51 may include a base plate and side plates connected to the base plate, the base plate and side plates forming a receiving cavity. The housing 51 has an opening communicating with the receiving cavity, and the cover plate 53 can be placed over the opening to close the receiving cavity. A positive electrode, a negative electrode, and a separator can be formed into an electrode assembly 52 using a winding or stacking process. The electrode assembly 52 is encapsulated within the receiving cavity. Electrolyte is immersed in the electrode assembly 52. The battery 5 may contain one or more electrode assemblies 52, which can be selected by those skilled in the art according to specific practical needs.
[0113] In some implementations, the batteries can be assembled into battery modules, and the number of batteries contained in a battery module can be one or more, the specific number of which can be selected by those skilled in the art according to the application and capacity of the battery module.
[0114] Figure 5 This is battery module 4, used as an example. (See reference...) Figure 5 In battery module 4, multiple batteries 5 can be arranged sequentially along the length of battery module 4. Of course, they can also be arranged in any other manner. Furthermore, these multiple batteries 5 can be fixed in place using fasteners.
[0115] Optionally, the battery module 4 may also include a housing with a receiving space in which a plurality of batteries 5 are received.
[0116] In some embodiments, the battery modules described above can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be one or more, the specific number of which can be selected by those skilled in the art according to the application and capacity of the battery pack.
[0117] Figure 6 and Figure 7 This is battery pack 1 as an example. (See reference...) Figure 6 and Figure 7 The battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box includes an upper body 2 and a lower body 3, with the upper body 2 covering the lower body 3 to form a closed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.
[0118] In addition, this application also provides an electrical device, which includes at least one of the battery, battery module, or battery pack provided in this application. The battery, battery module, or battery pack can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0119] As the electrical equipment, batteries, battery modules, or battery packs can be selected according to their usage requirements.
[0120] Figure 8 This is an example of an electrical device. The device could be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the device's requirements for high power and high energy density batteries, a battery pack or battery module can be used.
[0121] Another example device could be a mobile phone, tablet, or laptop. These devices typically require a slim and lightweight design and can be powered by a battery.
[0122] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0123] Example 1
[0124] Weigh the corresponding sodium source (Na2CO3) and manganese source (Mn2O3) according to Na:Mn (molar ratio) = 1:1, ball mill at 400 rpm for 2 hours, put the resulting mixture into a muffle furnace, heat it to 900℃ at 5℃ / min under argon protection, hold it at that temperature for 15 hours, and then let it cool naturally to room temperature to obtain the O'3 phase material.
[0125] Subsequently, the O'3 phase material was heated to 900°C at a rate of 5°C / min in air, held at that temperature for 10 hours, and then allowed to cool naturally to room temperature to obtain the positive electrode active material.
[0126] Example 2
[0127] Manganese-based sodium electrochemical materials were prepared according to the method in Example 1, except that the second sintering temperature was adjusted to 850°C.
[0128] Example 3
[0129] Manganese-based sodium electrochemical materials were prepared according to the method in Example 1, except that the second sintering temperature was adjusted to 950°C.
[0130] Example 4
[0131] Manganese-based sodium electrochemical materials were prepared according to the method in Example 1, except that the second sintering time was adjusted to 7 hours.
[0132] Example 5
[0133] Manganese-based sodium electrochemical materials were prepared according to the method in Example 1, except that the second sintering time was adjusted to 9 hours.
[0134] Example 6
[0135] Manganese-based sodium electrochemical materials were prepared according to the method in Example 1, except that the second sintering time was adjusted to 12 hours.
[0136] Example 7
[0137] Manganese-based sodium electrochemical materials were prepared according to the method in Example 1, except that the corresponding sodium source (Na2CO3) and manganese source (Mn2O3) were weighed according to the molar ratio of Na:Mn = 0.85:1.
[0138] Example 8
[0139] Manganese-based sodium electrochemical materials were prepared according to the method in Example 1, except that the corresponding sodium source (Na2CO3), manganese source (Mn2O3), and titanium source (TiO2) were weighed according to the ratio of Na:Mn:Ti = 1:0.9:0.1.
[0140] Comparative Example 1
[0141] Weigh the corresponding sodium source (Na2CO3) and manganese source (Mn2O3) according to the Na:Mn (molar ratio) = 1:1, and ball mill them at 400 rpm for 2 hours. Place the resulting mixture in a muffle furnace, heat it to 900℃ at 5℃ / min under argon protection, hold it at that temperature for 15 hours, and then allow it to cool naturally to room temperature to obtain the O'3 phase material with the chemical formula NaMnO2.
[0142] Test case
[0143] 1. Morphological characteristics
[0144] SEM images were used for testing: Field emission scanning electron microscope (Zeiss Gemini 360) was used for testing according to JY / T010-1996 standard.
[0145] 2. Crystal phase characterization
[0146] Grind the sample to be tested into a fine powder in an agate mortar and pestle in a drying room or glove box, then pass it through a 350-mesh sieve. Take an appropriate amount of the sieved sample and place it in the center of the sample holder groove, ensuring the loose sample powder is slightly higher than the sample holder plane. Gently press a glass slide onto the sample surface to level it with the frame plane, and scrape off any excess powder. After sample preparation, use a Brucker D8A_A25 X-ray powder diffractometer (Brucker AxS, Germany) with CuK... α X-rays are the radiation source, and the wavelength of the X-rays is... The 2θ angle range is 5° to 60°, and the scanning rate is 4° / min. After the test is completed, the space group of the sample can be confirmed by comparing the XRD diffraction peaks of the sample with the standard card of the XRD analysis software.
[0147] 3. Air stability test
[0148] The positive electrode active material was placed in humid air (humidity > 60%) at room temperature for 10 days before XRD and scanning electron microscopy tests were performed.
[0149] 4. Volume retention test after 50 cycles
[0150] At 25℃, after fabricating a coin cell using layered oxide cathode active material, it was charged to 4.3V at a constant current density of 10mA / g, and then discharged to 2V at a constant current density of 10mA / g, yielding the discharge specific capacity C0 of the coin cell. Subsequently, it underwent 50 charge-discharge cycles at a constant current density of 10mA / g, and the discharge specific capacity C1 of the 50th cycle was recorded. The capacity retention rate of the layered oxide cathode active material after 50 cycles is calculated as C1 / C0.
[0151] The button cell is prepared according to the steps shown below.
[0152] Preparation of the positive electrode sheet: The layered oxide positive electrode active material, conductive agent carbon black (Super P), and binder polyvinylidene fluoride (PVDF) are thoroughly mixed in an appropriate amount of solvent NMP at a mass ratio of 80:15:5 to form a uniform positive electrode slurry; the positive electrode slurry is uniformly coated on the surface of the positive electrode current collector aluminum foil, and after drying and cold pressing, it is punched into a disc with a diameter of 14mm to obtain the positive electrode sheet.
[0153] Negative electrode: Made of metallic sodium.
[0154] Preparation of electrolyte: Equal volumes of ethylene carbonate (EC) and diethyl carbonate (DEC) are mixed to obtain an organic solvent. Then, NaClO4 is dissolved in the organic solvent to prepare an electrolyte with a concentration of 1 mol / L.
[0155] Separator membrane: Porous polyethylene membrane is used as the separator membrane.
[0156] Preparation of button cell: Stack the above-mentioned positive electrode, separator, and negative electrode in sequence, so that the separator is placed between the positive electrode and the negative electrode to play a role in isolation. Add the prepared electrolyte to complete the preparation of button cell.
[0157] The structures of the positive electrode active materials in Examples 1-9 and Comparative Example 1, as well as the test results of the batteries, are shown in Table 1.
[0158] Table 1
[0159]
[0160] In conclusion, comparing Examples 1-8 with Comparative Example 1, it can be seen that the cycle capacity retention rate of the battery proposed in this application is significantly higher than that of the comparative example. This indicates that by forming a coating phase on at least a portion of the surface of the bulk phase, this application can reduce the probability of sodium reacting with carbon dioxide and water in the air and improve the air stability of the positive electrode active material.
[0161] As can be seen from the comparison of Examples 1-6, by adjusting the temperature and time of the second sintering, it is possible to increase the content of the coating phase on the surface of the bulk phase, form a uniform coating phase on the surface of the bulk phase, thereby improving the coating effect and enhancing the air stability of the positive electrode active material.
[0162] As can be seen from the comparison between Example 1 and Example 7, by adjusting the mass ratio of sodium source and manganese source, the element content of bulk phase and coated phase can be adjusted, thereby improving the air stability of positive electrode active material.
[0163] As can be seen from Example 8, when the bulk phase and the coating phase contain doping elements, the coating phase can also reduce the probability of sodium reacting with carbon dioxide and water in the air, thereby improving the air stability of the positive electrode active material.
[0164] Figure 9 The XRD test results are for Example 1. Figure 10 The XRD test results are for Comparative Example 1. Figure 11 The image shows a comparison of the XRD test results of Example 1 and Comparative Example 1. The XRD peak intensity of Example 1 is higher than that of Comparative Example 1, and Comparative Example 1 has more new impurity peaks, indicating that the bulk structure is damaged.
[0165] Figure 12 This is a SEM image of the positive electrode active material in Example 1 after being placed at room temperature for 10 days. Figure 13 The image shows an SEM image of the positive electrode active material in Comparative Example 1 after being placed at room temperature for 10 days. The comparison shows that the surface of the positive electrode active material in Example 1 is smoother and has almost no cracks; the surface of the positive electrode active material in Comparative Example 1 has products after reacting with air and the material has more cracks, indicating that the positive electrode active material in Example 1 has better stability in air.
[0166] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and not to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. These modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application, and they should all be covered within the scope of the claims and specification of this application. In particular, as long as there is no structural conflict, the various technical features mentioned in the embodiments can be combined in any way. This application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.
Claims
1. A positive electrode active material, characterized in that, It includes a bulk phase and a coating phase located on at least a portion of its surface, wherein the bulk phase includes Na. x1 Mn y1 X z O 2+δ1 , the Na x1 Mn y1 X z O 2+δ1 The coating phase includes the O'3 phase, with a 0.8 ≤ x1 ≤ 1, 0.8 ≤ y1 ≤ 1, 0 ≤ z ≤ 0.2, and -0.1 ≤ δ1 ≤ 1. X includes one or more of Ti, Zr, Ge, and Sn. The coating phase includes Na. x2 Mn y2 X z O 2+δ2 , the Na x2 Mn y2 X z O 2+δ2 Including phase P2, 0.4≤x2≤0.7, 0.85≤y2≤1, -0.1≤δ2≤1; The intensity of peak 001 in the X-ray diffraction pattern of the O'3 phase is S1, and the intensity of peak 002 in the X-ray diffraction pattern of the P2 phase is S2. S1 and S2 satisfy 2≤S1 / S2≤6. The 2θ value corresponding to peak 001 in the X-ray diffraction pattern is 15.8°-16.8°, and the 2θ value corresponding to peak 002 is 15.3°-16.3°.
2. The positive electrode active material according to claim 1, characterized in that, The volume average particle size D of the positive electrode active material V 50 is 0.2μm-3μm.
3. The positive electrode active material according to claim 1, characterized in that, The space groups for the O'3 phase and the P2 phase are C2 / m and P63 / mmc, respectively.
4. The positive electrode active material according to any one of claims 1-3, characterized in that, The peak intensity of 001 in the X-ray diffraction pattern of the O'3 phase is S1, and the peak intensity of 002 in the X-ray diffraction pattern of the P2 phase is S2. S1 and S2 satisfy 3≤S1 / S2≤4.
5. The 2θ value corresponding to peak 001 in the X-ray diffraction pattern is 15.8°-16.8°, and the 2θ value corresponding to peak 002 is 15.3°-16.3°.
5. A method for preparing a positive electrode active material, characterized in that, include: Sodium and manganese sources are mixed and sintered for the first time in an inert atmosphere to form a bulk phase; The bulk phase is subjected to a second sintering in an oxygen-containing atmosphere to form a coating phase on at least a portion of the surface of the bulk phase; wherein the bulk phase comprises Na. x1 Mn y1 O 2+δ1 , the Na x1 Mn y1 O 2+δ1 It includes the O'3 phase, 0.8≤x1≤1, 0.8≤y1≤1, -0.1≤δ1≤1; the coating phase includes Na. x2 Mn y2 O 2+δ2 , the Na x2 Mn y2 O 2+δ2 Including phase P2, 0.4≤x2≤0.7, 0.85≤y2≤1, -0.1≤δ2≤1; or, Sodium source, manganese source and X source are mixed and sintered for the first time in an inert atmosphere to form a bulk phase; The bulk phase is subjected to a second sintering in an oxygen-containing atmosphere to form a coating phase on at least a portion of the surface of the bulk phase; wherein the bulk phase comprises Na. x1 Mn y1 X z O 2+δ1 , the Na x1 Mn y1 X z O 2+δ1 The coating phase includes the O'3 phase, with 0.8 ≤ x1 ≤ 1, 0.8 ≤ y1 ≤ 1, 0 < z ≤ 0.2, -0.1 ≤ δ1 ≤ 1, and X includes one or more of Ti, Zr, Ge, and Sn; the coating phase includes Na. x2 Mn y2 X z O 2+δ2 , the Na x2 Mn y2 X z O 2+δ2 Including phase P2, 0.4≤x2≤0.7, 0.85≤y2≤1, -0.1≤δ2≤1; The intensity of peak 001 in the X-ray diffraction pattern of the O'3 phase is S1, and the intensity of peak 002 in the X-ray diffraction pattern of the P2 phase is S2. S1 and S2 satisfy 2≤S1 / S2≤6. The 2θ value corresponding to peak 001 in the X-ray diffraction pattern is 15.8°-16.8°, and the 2θ value corresponding to peak 002 is 15.3°-16.3°.
6. The method according to claim 5, characterized in that, The conditions for the first sintering include: a temperature of 800℃-1000℃ and a time of 12h-18h.
7. The method according to claim 5 or 6, characterized in that, The conditions for the first sintering include: a temperature of 850℃-950℃ and a time of 13h-17h.
8. The method according to claim 5 or 6, characterized in that, The oxygen-containing atmosphere includes oxygen or air.
9. The method according to claim 5 or 6, characterized in that, The conditions for the second sintering include: a temperature of 900℃-1000℃ and a time of 8h-15h.
10. The method according to claim 5 or 6, characterized in that, The conditions for the second sintering include: a temperature of 900℃-950℃ and a time of 9h-12h.
11. The method according to claim 5 or 6, characterized in that, The method satisfies one or more of the following conditions: The sodium source includes one or more of Na2CO3, NaHCO3, NaOH, and Na2O2; The manganese source includes one or more of Mn2O3, Mn3O4, MnO, and MnO2.
12. The method according to claim 5 or 6, characterized in that, The amounts of the sodium source and the manganese source are such that the atomic molar ratio of Na to Mn is 1:0.8-1.
2.
13. A positive electrode plate, characterized in that, It comprises: the positive electrode active material according to any one of claims 1-4 or the sodium secondary positive electrode active material prepared by the method according to any one of claims 5-12.
14. A battery, characterized in that, Includes the positive electrode sheet as described in claim 13.
15. An electrical appliance, characterized in that, Includes the battery as described in claim 14.
Citation Information
Patent Citations
Sodium-ion battery positive electrode material as well as preparation method and application thereof
CN116581274A
Positive electrode material, preparation method thereof and sodium ion battery
CN117317200A